Patients Undergoing Cesarean Delivery After Exposure to Oxytocin During Labor Require Higher Postpartum Oxytocin Doses. Issue 3 (September 2018) - Foley, A.; Gunter, A.; Nunes, K.J.; Shahul, S.; Scavone, B.M.
Abstract : ( Anesth Analg . 2018;126:920–924) The effective dose in 90% of patients (ED90) of oxytocin infusion after cesarean delivery (CD) without labor has been reported to be 17.4 IU/h. A recent study has demonstrated an increased ED90 of 44.2 IU/h for patients who were exposed to oxytocin during labor and then progressed to CD. The University of Chicago Family Birth Center protocol for oxytocin administration in the third stage of labor calls for administration of 18 IU/h of oxytocin, with the option for doubling the infusion rate to 36 IU/h in cases of inadequate response. In this retrospective study, the authors determined the clinical relevance of increased dosing requirements for third-stage oxytocin among those patients who were exposed to oxytocin before CD versus those who were not, with the hypothesis that patients exposed to oxytocin before CD would require a higher infusion rate than called for in the protocol.